A study of the efficacy of external fixation in healing large, deep and unstable diabetic foot wounds - Patro, Byomokesh; Surana, Pankaj; Mahapatra, Kailash Chandra (International Surgery Journal, 2019)
Background: Infection of a diabetic foot wound heralds a poor outcome, early diagnosis and treatments are important. The aim of the study was to study the efficacy of external fixation in healing large, deep and unstable diabetic foot wounds. Methods: 50 patients with diabetic foot ulcer considered for the present study. Out of this 50 cases 25 are selected for external fixations (study group), after fulfilling the inclusion criteria and rest 25 cases are managed by posterior slab support. After reducing the infective load, the external fixator was applied as per application of external fixator procedure. The fixator is kept for 4 to 6 weeks. Daily dressings are done with advance dressing materials. Posterior slab group 25 patients are included having large, deep ulcers and unstable joints, to which posterior slabs were supported after proper and extensive debridement of wound under SA/LA. Results: DFU predominantly affects right lower limb than left lower limb. Both lower limbs affected in 4% cases. Because of different working environment males are more vulnerable to foot ulcerations. Out of 50 cases 48 (96%) of DFU are unilateral and 32 no of cases (64%) are predominantly occurs in right lower limb (Table 2). Out of 50 cases 38 no. of patient are males and 12 no. of patient are females. External fixator in exposed joint decreases the wounds in 52 days where as by posterior slab support 59 days. The mean surfaces are of the wound after therapy in study group is 75 cm2 and in control group it was 78 cm2. Conclusions: Large ulcers and exposed joints due to diabetic foot can be managed by external fixator for better prognosis than posterior slab method.